2016
DOI: 10.1103/physrevb.93.104517
|View full text |Cite
|
Sign up to set email alerts
|

Thermal evolution of antiferromagnetic correlations and tetrahedral bond angles in superconductingFeTe1xSex

Abstract: It has recently been demonstrated that dynamical magnetic correlations measured by neutron scattering in iron chalcogenides can be described with models of short-range correlations characterized by particular choices of four-spin plaquettes, where the appropriate choice changes as the parent material is doped towards superconductivity. Here we apply such models to describe measured maps of magnetic scattering as a function of two-dimensional wave vectors obtained for optimally superconducting crystals of FeTe1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
46
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(59 citation statements)
references
References 86 publications
12
46
1
Order By: Relevance
“…For the theory to be consistent, it is important that it should be able to describe not only the lack of magnetic ordering in FeSe, but also the appearance of magnetism under applied pressure and with Te doping. In this paper, we show that the recently proposed theory of the spin ferroquadrupolar (FQ) ground state for FeSe [25] indeed satisfies these requirements and successfully describes the evolution of the INS data as a function of Te doping in Fe(Te 1−x Se x ), in qualitative accord with the recent INS experiments [11].…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…For the theory to be consistent, it is important that it should be able to describe not only the lack of magnetic ordering in FeSe, but also the appearance of magnetism under applied pressure and with Te doping. In this paper, we show that the recently proposed theory of the spin ferroquadrupolar (FQ) ground state for FeSe [25] indeed satisfies these requirements and successfully describes the evolution of the INS data as a function of Te doping in Fe(Te 1−x Se x ), in qualitative accord with the recent INS experiments [11].…”
Section: Introductionsupporting
confidence: 66%
“…Remarkably, it was found that in nonsuperconducting Fe(Te 1−x Se x ) samples (due to excess of Fe), the magnetic correlations remain pinned at (π/2,π/2) [11]. The authors of Ref.…”
Section: Dynamical Spin-structure Factor and Comparison With Expermentioning
confidence: 99%
See 3 more Smart Citations